Comparison of computer-aided detection (CADe) capability for pulmonary nodules among standard-, reduced- and ultra-low-dose CTs with and without hybrid type iterative reconstruction technique. Issue 100 (March 2018) - Ohno, Yoshiharu; Aoyagi, Kota; Chen, Qi; Sugihara, Naoki; Iwasawa, Tae; Okada, Fumito; Aoki, Takatoshi
Highlights: The AIDR 3D has a significant positive effect on the nodule detection capability of the CADe system even when radiation dose is reduced. With the AIDR 3D method, 80 % CT examination radiation dose can be reduced without any degradation of detection efficiency of the CADe system. When applied AIDR 3D, sensitivities and false-positive rates were equal to or relatively better than those previously reported. When applied AIDR 3D, there were no significant differences of sensitivity between standard-dose CT without AIDR 3D and others. False-positive rate of ultra-low-dose CT with AIDR 3D was significantly higher than that of standard-dose CT with and without AIDR 3D. Abstract: Purpose: To directly compare the effect of a reconstruction algorithm on nodule detection capability of the computer-aided detection (CADe) system using standard-dose, reduced-dose and ultra-low dose chest CTs with and without adaptive iterative dose reduction 3D (AIDR 3D). Materials and methods: Our institutional review board approved this study, and written informed consent was obtained from each patient. Standard-, reduced- and ultra-low-dose chest CTs (250 mA, 50 mA and 10 mA) were used to examine 40 patients, 21 males (mean age ± standard deviation: 63.1 ± 11.0 years) and 19 females (mean age, 65.1 ± 12.7 years), and reconstructed as 1 mm-thick sections. Detection of nodule equal to more than 4 mm in dimeter was automatically performed by our proprietary CADe software. The utility of iterative reconstruction method for improving nodule detection capability, sensitivity and false positive rate (/case) of the CADe system using all protocols were compared by means of McNemar's test or signed rank test. Results: Sensitivity (SE: 0.43) and false-positive rate (FPR: 7.88) of ultra-low-dose CT without AIDR 3D was significantly inferior to those of standard-dose CTs (with AIDR 3D: SE, 0.78, p < .0001, FPR, 3.05, p < .0001; and without AIDR 3D: SE, 0.80, p < .0001, FPR: 2.63, p < .0001), reduced-dose CTs (with AIDR 3D: SE, 0.81, p < .0001, FPR, 3.05, p < .0001; and without AIDR 3D: SE, 0.62, p < .0001, FPR: 2.95, p < .0001) and ultra-low-dose CT with AIDR 3D (SE, 0.79, p < .0001, FPR, 4.88, p = .0001). Conclusion: The AIDR 3D has a significant positive effect on nodule detection capability of the CADe system even when radiation dose is reduced.